PS 09-02 BURDEN & CORRELATES OF DIAGNOSED & UNDIAGNOSED HYPERTENSION: OBSERVATION FROM AN URBAN AREA IN INDIA. (September 2016) - Chakraborty, Nilanjana; Mahapatra, Tanmay; Chakraborty, Kaushik; Mitra, Ramendra Nath; Thompson, Peter L.
Abstract : Objective: Hypertension is a silent major risk factor for cardiovascular and cerebro-vascular disease (CVD) related morbidity & mortality. The objectives of the study were to measure the prevalence of doctor diagnosed hypertension (DDH), undiagnosed hypertension and assessment of the associations of socio-demographic and behavioral factors. Design and Method: WHO classification of hypertension and gradations were used in the cross sectional study of 5347 adults of an established urban longitudinal population cohort of West Bengal, India. Information gathered from pre-tested questionnaire, anthropometry and brachial arterial blood pressure obtained with electronic sphygmomanometer. Results: Among the participants, 2083 (38.96%) were male and 3264 (61.04%) were female. 1712 (32.05%) were hypertensive, 1039 (19.48%) had DDH out of which 963 (92.69%) were on medications. Among DDH, 512 (49.28%) were uncontrolled hypertensives while majority on treatment .Undiagnosed hypertensives were 664 (12.42%). Increasing age is associated with DDH [AOR = 1.08, 95% CI: (1.08–1.09), p < .0001] and overall hypertension [AOR = 1.09, 95% CI: (1.08–1.10), p < .0001]. Ex-smokers and ex-drinkers were associated with DDH [AOR = 1.60, 95% CI: (1.15–2.22), p = 0.0055] and [AOR = 1.74, 95% CI: (1.14–2.63), p = 0.0096] respectively. Always snorers were associated with DDH [AOR = 2.05, 95% CI: (1.71–2.47), p < .0001] and overall hypertension [AOR = 1.71, 95% CI: (1.44–2.02), p < .0001]. Obese persons were associated with DDH [AOR = 3.21, 95% CI: (2.48–4.16), p < .0001] and overall hypertension [AOR = 2.85, 95% CI: (2.44–3.63), p < .0001]. Participants consuming additional salt always [AOR = 1.85, 95% CI: (1.45–2.36), p < .0001] or sometimes [AOR = 1.66, 95% CI: (1.25–2.20), p = 0.0005] with food were associated with undiagnosed hypertension. Conclusions: Nearly one third of the adult cohort was hypertensive and one fifth was doctor diagnosed. Half of DDH remained uncontrolled while 93% being on treatment. Majority of risk factors noted were reversible therefore targeted evidence based intervention is expected to reduce the burden of hypertension and related complications.